A review of the causes of construction waste generation in Nigeria and recommendations. Issue 2 (26th May 2021) - Chidiobi, Chibuike; Booth, Colin; Lamond, Jessica
Abstract : The causes of construction waste (CW) in Nigeria have been a major topic for researchers over the last 15 years. However, no effort had been made to analyse these studies to understand the trends. A structured review of 30 research studies investigating the causes of CW in Nigeria from 2005 to 2019 was therefore undertaken. The findings indicated that the majority of the articles were published in journals. Questionnaire survey and descriptive statistics were the dominant data collection and analytical methods, respectively. Geographically, data collection focused on Abuja and Lagos. There was a significant focus on the causes of waste generation in the construction stage rather than the design and procurement stages. Late design changes, purchase of substandard materials and inadequate supervision were the underlying causes of waste in the design, procurement and construction stages, respectively. It is recommended that future studies should focus more on minimisation solutions from different perspectives due to the potential increase in construction activities in Nigeria. This study will guide researchers and practitioners to understand the trends of studies on the causes of CW in Nigeria.